Análisis de un sistema de control web orientado al registro escolar y gestiones académicas de los estudiantes en la Unidad Educativa La Ronda de la ciudad de Babahoyo - Murillo Piza, Víctor Ariel (2020)
Academic management control system in the educational unit "La ronda", currently they carry out most of their academic processes manually, so an analysis must be carried out for a computer system that meets the requirements of educational institutions. Above all, at present the field of computer science has had great important advances that have helped in some roles in different institutional and educational areas. Given the great advances that Computer Science is having in development, it has been decided to focus the case study on a Web System aimed at school registration and academic efforts for the benefit of teaching in the Educational Unit "La ronda", with the objective of contributing to the academic improvement of the Institution, and opening new horizons in the teaching of the inclusion of technology. The analysis of the educational system to solve the problems detected at the time of manual elaboration and therefore improve the processes that are involved in the communication that exists between teachers and students, as well as the intervention of parents or representatives with the reason for keeping them informed of the academic efforts of their clients. Therefore, it is concluded that with this proposed analysis it will allow to implement a good system so that it fulfills its requirements in a simpler, faster, and more interactive way in the management of the system with the user at the time they use it.